Selecting Initial Breeding Sources for Morning Varieties from The Potato Variety Sample Collection - Sirojiddin Turdikulovich Jurayev; Rasul Abdujabborovich Karimov (Web of Journals Publishing, 2023)
The article talks about the method of selection of initial selection resources for early varieties from the collection of potato variety samples.
Keywords: Potatoes, potato crops, variety, sample, collection, selection.